Análise documental de textos literários infanto-juvenis: perspectivas metodológicas com vistas à identificação do tema - Alves, Roberta Caroline Vesú [UNESP] (2008)
The school library users request an infant-juvenile literature according to themes expressing their reading interests. To explain this need for information, the study of the documentary analysis of content was exploited for the identification of themes, focusing the strategy of textual exploitation based on the gerative sense course in infant-juvenile literature, in order to make its content accessible. The research problem investigated solutions for a suitable documentary analysis of content before implied terms which are necessary to the identification of themes. Applying, in this case, the methodology of exploratory study, which considered the interdisciplinarity among Science of Information, Textual Linguistics, Narrative and Discursive Semiotics, and Discursive Semantics, because together they elucidate the methods of identification of the document content and also explain the disposition and the theme of the fiction texts. The hypothesis saying that the gerative sense course makes the textual structure evident, alerting to the important parts of the narrative and its thematics, was verified. It was found, therefore, that the objectives of research to analyze the theories of the gerative sense course for the identification of themes in infant-juvenile literature apply to the proposal affirming that these theories are part of the method to identify the themes. The outcome of the corpus analyzed shows that the gerative sense course is very helpful to identify the textual structure, as well as the main theme, together with other implicit themes which are considered important.